Don't be a Stickler! - Chong, Chelsea Su Yeung (Nanyang Technological University, 2023)
Don't be a Stickler! is a project that delves into the importance of mobility and how walking sticks have become a crucial tool for maintaining independence and quality of life for individuals with mobility impairments. In addition to discussing the technical aspects of walking sticks, this book will also cover the broader implications of mobility aids on quality of life. By highlighting the ways in which walking sticks can promote independence, confidence, and mobility, I hope to inspire readers to embrace the many benefits of these simple yet powerful tools.